Long-term in vivo operation of implanted cardiac nanogenerators in swine. (December 2021) - Li, Jun; Hacker, Timothy A.; Wei, Hao; Long, Yin; Yang, Fan; Ni, Dalong; Rodgers, Allison; Cai, Weibo; Wang, Xudong
Abstract: Implantable nanogenerators (i-NG) provide power to cardiovascular implantable electronic devices (CIEDs) by harvesting biomechanical energy locally eliminating the need for batteries. However, its long-term operation and biological influences on the heart have not been tested. Here, we evaluate a soft and flexible i-NG system engineered for long-term in vivo cardiac implantation. It consisted of i-NG, leads, and receivers, and was implanted on the epicardium of swine hearts for 2 months. The i-NG system generated electric current throughout the testing period. Biocompatibility and biosafety were established based on normal blood and serum test results and no tissue reactions. Heart function was unchanged over the testing period as validated by normal electrocardiogram (ECG), transthoracic ultrasound, and invasive cardiac functional measures. This research demonstrates the safety, long term operation and therefore the feasibility of using i-NGs to power the next generation CIEDs. Graphical Abstract: A soft and flexible implantable nanogenerator (i-NG) system engineered for long-term in vivo cardiac implantation was evaluated. The system, which exhibited great potential of real-time detecting ischemic heart attack and powering small electronics, was implanted on the epicardium of swine hearts for 2 months. Blood chemistry and tissue pathology analysis demonstrated good biocompatibility. Heart function was unchanged over the course of study, as evidenced by electrocardiogram (ECG), transthoracic ultrasound and cardiac pressure–volume loop analysis. This work provides a critical step for the potential translation of i-NG system toward clinical applications. ga1 Highlights: A soft and flexible NG was implanted on the epicardium of swine hearts and operated consistently for 2 months. The in vivo performance of the implantable NG (i-NG) was monitored over time enabled by leads and under-skin receivers. Heart functions and chemistry analyses demonstrated long-term biosafety and biocompatibility of the cardiac NG implants. The i-NG system and exhibited great potential of real-time detecting ischemic heart attack and powering electronics.